Croatia: The Experiences of Other Countries as a Guide to the Euro Area Accession Process - Žunić Kovačević, Nataša (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
After short introduction author gives review and analyses experiences of Croatia in a process of euro area accession. It is pointed that the conditions for entry into the Euro Area remained unchanged, so Croatia followed the path to the euro based on the criteria set out in the Maastricht Treaty. This paper examined with an overview of the experiences of Croatia in a process of euro area accession by giving a review of Croatian National Bank with relation to European Central Bank with section explaining the process of acquiring experiences from other eurozone member states. After the section on outcomes related to the introduction of the Euro and banking union special focus is given to the participation in the exchange rate mechanism – ERM II with described process of established close cooperation between the ECB and the HNB. The role of the HNB in the unified supervisory mechanism with Single Resolution Mechanism and the Croatian responsible national authorities chapter is central part of the paper. It is emphasized that ERM II was important preparatory phase towards euro adoption in Croatia. Concluding remarks are about positive effects of adopting the euro in Croatia in a short-term, with message on the long-term effects that depend on the domestic capability for changes. Keywords: Croatia’s euro area accession, HNB, ECB, exchange rate mechanism